Green's Function for A Piecewise Continous Potential via Integral Equations Method - Benali Brahim; Mohammed Tayeb Meftah; Rai Vandana (Journal of the Indonesian Mathematical Society, 2018)
The aim of this work is to provide Green's function for the Schrodingerequation. The potential part in the Hamiltonian is piecewise continuous operator.It is a zero operator on a disk of radius "a" and a constant V0 outside this disk (intwo dimensions). We have used, to construct the Green's function, the technique ofthe integral equations. We have respected the boundary conditions of the problem.The discrete spectra of the Hamiltonian operator have been also derived.